Analysis of The Influence of Electronic Customer Satisfaction, Application Perceived Value and Electronic Service Quality on Electronic Customer Loyalty of Ruang Guru Application Users - Ekasari, Silvia; Dewi, Luh Komang Candra; Efendi, Bahtiar; Sulistiarini, Emma Budi; Jodi, I Wayan Gede Antok Setiawan (Institut Riset dan Publikasi Indonesia, 2024)
The purpose of this study is to determine whether the perceived value and quality of e-services impact e-customer loyalty and satisfaction. All users of the educational platform constitute the population studied. In this survey, non-probability sampling technique was used. 100 samples were used in this investigation. Questionnaire was the method used in this study to collect data. Quantitative method was used in this study. Partial least squares (PLS) is a statistical method used with the support of SmartPLS. Several conclusions are drawn from this study, including: Customer satisfaction is directly affected by e-service quality. Electronic customer satisfaction is directly affected by perceived value. E-customer loyalty is directly affected by e-service quality. Electronic customer loyalty is directly influenced by perceived value. Customer loyalty is directly affected by electronic customer satisfaction. Through e-customer satisfaction, e-service quality indirectly affects e-customer loyalty. Thanks to e-customer satisfaction, perceived value indirectly affects e-customer loyalty. Research results show that customer satisfaction and loyalty are influenced by the extent to which they perceive positive value when using educational platform services to meet their learning needs. their.